Simulación numérica del funcionamiento hidráulico de una rejilla de efecto Coanda utilizando metodología CFD - Samaniego Burneo, Santiago Germán (2015)
According to hydraulic high throughput studies, it has been demonstrated that the use of Coanda-Effect Screens in intake works, are extremely reliable and efficient, due to numerous advantages that these has over conventional grids. The present work aims at the analysis of the results of captured flow and flow derived from an intake works using Coanda-Effect Screens, obtained from a numerical simulation methodology using CFD (Computational Fluid Dynamics). These results were validated with the mathematical models proposed by Tony Wahl in 2001 and 2013. For the CFD simulation the 14.5 version ANSYS software was used, which includes the CFX module for solving fluid systems. The theoretical results were obtained using the Hydraulic Performance of Coanda Effect Screens software, made by Wahl. It was proved that the results of the simulation were satisfactory regarding the theoretical results. This study is one of the first CFD projects at the Universidad Técnica Particular de Loja.